Perancangan Perangkat Lunak Sistem Parkir Kendaraan Menggunakan Metode Design Thinking - Maulana, Arlan; Ahmad Syazili; Muhamad Ariandi (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
The first parking system implemented in Indonesia was a manual or traditional parking system. Just like the parking system in Air Kumbang District which still uses a manual parking system. This causes crimes such as motorbike theft and the absence of complete, informative and interactive parking information which is one of the problems with manual parking. Designing a more modern parking system using the Design Thinking method can be used to overcome this problem. Design Thinking is a human-centered approach method. Implementing this design thinking method involves 5 process stages consisting of data collection (emphatize), definition and analysis of the problem (define), solution stage (ideate), creating an interface design (prototype) and testing (testing). This method can be applied to various types of organizations to improve the process of creativity, problem solving, leadership and innovation. Based on research data, it shows that the level of user satisfaction for designing vehicle parking system software with an overall Single Ease Question score from the first user is 6.5 , the second user is 6.6 and the third user is 6.5, with the average of the three Single Ease Question scores being 6.5 on a scale of 1-7. This states that it is accepted by users and easy to understand. By implementing a parking system using the Design Thinking method, it is hoped that it can create a sense of comfort and ensure optimal user safety, so that users can carry out activities efficiently.